Use of an authorial training technology during technical and tactical training of women epee fencers - Semeryak, Z.; Briskin, Y.; Pityn, M.; Vaulin, O. (SportLogia, 2013)
Fencing belongs to group of martial arts with variable conditions of competitive activities, that determines priority in training structure of sportsmen opportunities for effective realization of tactical and technical set of moves. Level of rivalry in fencing competitions in Ukraine on all kinds of weapon, including epee is very low, this must be related to the problem of absence of qualified program of training on previous stages of long-term perfection. It indicates on the problem of accented review of scientific questions of effective training of qualified sportsmen that in future would be able to realize their individual opportunities on national and international levels. Possibility of accented increase of specialized load on sportsmen training should be considered on stage of specialized basic training. As follows, necessity of increasing effective training and results of competitive activity of qualified women epee fencers form a relevant scientific and practical task for technical and tactical improvement of sportsmen on stage of specialized basic training with account of structure and content of competitive activity of modern fencing.